Shear Strength of Unreinforced Masonry Wall Retrofitted with Fiber Reinforced Polymer and Hybrid Sheet - Choi, Chang Sik; Lee, Dongkeun; Choi, Hyun-Ki; Choi, Yun-Cheul (International Journal of Polymer Science, 2015)
Unreinforced masonry (URM) structures represent a significant portion of existing historical structures around the world. Recent earthquakes have shown the need for seismic retrofitting for URM structures. Various types of strengthening methods have been used for URM structures. In particular, a strengthening technique using externally bonded (EB) fiber reinforced polymer (FRP) composites has attracted engineers since EB FRP materials effectively enhance the shear strength of URM walls with negligible change to cross-sectional area and weight of the walls. Research has been extensively conducted to determine characteristics of URM walls strengthened with EB FRP materials. However, it is still difficult to determine an appropriate retrofitting level due to the complexity of mechanical behavior of strengthened URM walls. In this study, in-plane behavior under lateral loading was, therefore, investigated on a full-scale nonstrengthened URM wall and URM walls retrofitted with two different FRP materials: carbon (CFRP) and hybrid (HFRP) sheets. The test results indicated that both FRP composites were effective in increasing shear strength in comparison with the control specimen. However, better performance was obtained with HFRP compared to CFRP. In addition, an equation for estimating effective strain was proposed, and the theoretical results were in good agreement with the experimental ones.